Biological variation and reference change value of the estimated glomerular filtration rate in humans: A systematic review and meta-analysis - Thöni, Stefanie; Keller, Felix; Denicolò, Sara; Buchwinkler, Lukas; Mayer, Gert (Frontiers in Medicine, 2022)
Background Knowledge of the biological variation of serum or plasma creatinine (Cr) and the estimated glomerular filtration rate is important for understanding disease dynamics in CKD. The aim of our study was to determine the magnitude of random fluctuation of eGFR by determining its reference change value (RCV). Methods We performed a systematic review and meta-analysis of studies on biological variation of Cr. Relevant studies were identified by systematic literature search on PubMed. Additional studies were retrieved from the EFLM Biological Variation Database. Random-effects meta-analysis was conducted to derive an overall estimate of intra-individual variation of creatinine (CVICr). Based on our estimate of CVICr and RCV for Cr, the RCV for the eGFR was determined. Results Among identified studies, 37 met our inclusion criteria. Meta-analysis of all studies yielded a CVICr of 5.2 % (95 % confidence interval [CI] 4.6 % - 5.8 %), however high between-study heterogeneity (I2 = 82.3 %) was found. Exclusion of outliers led to a significant reduction of heterogeneity while still including 85 % of all studies and resulted in a slightly lower CVICr of 5.0 % (95 % CI 4.7 % - 5.4 %). Assuming an analytical variation of CVA 1.1 %, we found an overall RCV for eGFR of ± 16.5 %. After exclusion of outlier studies, we found a minimum conservative RCV for eGFR of ± 12.5 %. Conclusion The RCV of the eGFR represents a valuable tool for clinicians to discern true changes in kidney function from random fluctuation.